THE DISTRIBUTION OF PARTIAL MELT IN A GRANITIC SYSTEM: THE APPLICATION OF LIQUID PHASE SINTERING THEORY - Jurewicz S.R.; Watson E.B. (My University, 1985)
Two series of experiments, four crystallization and four partial melting, were performed at 1000°C and 10 kilobars in the quartz-alkali feldspar-granitic melt system in order to determine the equilibrium melt distribution and textural adjustment processes. The melt distribution in both types of experiments was characterized by melt residing at grain edge intersections and in a few large pools scattered throughout the sample. Wetting angle measurements from both sets of experiments gave values of 44, 49, and 59 degrees for the feldspar/feldspar, feldspar/quartz, and quartz/quartz wetting angles, respectively. Interparticle welding, a process consistent with the measured wetting angles, resulted in the formation of a skeleton of solid grains with very few unattached grains in any sample. Analysis of wetting angle distributions indicates that the longest duration experiments closely approached textural equilibrium and that the distributions of observed wetting angles from both sets of experiments were nearly identical.